Study on Estimation of Milk Production Based on Heart Girth Measurement and Udder Size of Fries Holland Dairy Cows - Aunurohman, Hudri; Djatmiko, OE (ANIMAL PRODUCTION, 2002)
An experiment entitled âStudy on Estimation of Milk Production Based on Heart Girth Measurement and Udder Size of Fries Holland Dairy Cows â has been carried at Karanglewas District Banyumas Regency. The objectives of this experiment were (1) to predict milk production of Fries Holland cows based on measurement of heart girth and udder size; (2) to complete information in attempting milk production estimation, especially Fries Holland cows; (3) to help the publics in case of productive cows selection. The material of this experiment was 40 heads of Fries Holland cows, at age of 3 years up to 5 years old. The result of this experiment (after the milk product data were corrected into 305 days lactation), showes that the average of heart girth was 180.20 Â± 7.06 cm; udder size was 89.03 Â± 23.35 dm2 and milk production was 2326.54 Â± 331.79 litters. The data analysis indicated that correlation coefisient r = 0.87 and determination coefisient (R2) = 0,7651 and the multiple regression equation : Y = 1465.66 + 1.42 X1+ 6.79 X2. From the result of this experiment, if could be conclude that udder size parameter was the best variable of milk production estimation compared to heart girth and if can be used to estimated milk production. (Animal Production 4(1): 32-35 (2002)Key words : milk production, heart girth, udder size, fries holand